Uma abordagem dirigida por modelos para gerência de variabilidade e execução de processos de software - Santos, Wanderson Câmara dos (2011)
This dissertation presents a model-driven and integrated approach to variability management, customization and execution of software processes. Our approach is founded on the principles and techniques of software product lines and model-driven engineering. Model-driven engineering provides support to the specification of software processes and their transformation to workflow specifications. Software product lines techniques allows the automatic variability management of process elements and fragments. Additionally, in our approach, workflow technologies enable the process execution in workflow engines. In order to evaluate the approach feasibility, we have implemented it using existing model-driven engineering technologies. The software processes are specified using Eclipse Process Framework (EPF). The automatic variability management of software processes has been implemented as an extension of an existing product derivation tool. Finally, ATL and Acceleo transformation languages are adopted to transform EPF process to jPDL workflow language specifications in order to enable the deployment and execution of software processes in the JBoss BPM workflow engine. The approach is evaluated through the modeling and modularization of the project management discipline of the Open Unified Process (OpenUP)